2020
DOI: 10.1080/14786419.2020.1782406
|View full text |Cite
|
Sign up to set email alerts
|

Semi-synthetic diversification of coronarin D, a labdane diterpene, under Ugi reaction conditions

Abstract: The prevalence of 5-hydroxydihydrofuran-2(3H)-one moiety in natural products is exploited for the first time using coronarin D, a labdane diterpene, to afford Ugi reaction product 1a and interrupted Ugi product 2a. The potential of the Ugi reaction was further extended to Lphenylalanine, 2-aminopyridine, and D-glucosamine, which afforded Ugi reaction products 3a-f, 4, and 5a-d, respectively. Cytotoxicity studies in RAW cells reveal that compounds 3e and 5b were non-toxic up to 50 µM, and these compounds were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…For instance, isocyanide‐based multicomponent reactions (I‐MCR) have been used for the synthesis of triterpene and marine natural products derivatives, although such reports remain limited. [ 5–9 ]…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, isocyanide‐based multicomponent reactions (I‐MCR) have been used for the synthesis of triterpene and marine natural products derivatives, although such reports remain limited. [ 5–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] In 2020, Veena et al used coronarin D 6 , which is a labdane diterpene to afford the imidazo[1,2‐ a ]pyridine 8 in 30% yield (Scheme 1B). [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Idippily et al synthesized a series of copalic acid (Figure 1) derivatives and found p‐ methoxyphenylamino copalic amide effectively restrained prostate cancer cell growth, possibly by inhibited the chaperone activity of α‐crystallin [33] . Other semi‐synthetic derivatives of labdanes also have been reported [34–38] . However, the anti‐tumor activities and mechanisms of action of alepterolic acid and its derivatives have been rarely reported to date.…”
Section: Introductionmentioning
confidence: 99%